The impact of cuts in legal aid funding of private family law cases. Issue 1 (2nd January 2019) - Wong, S.; Cain, R.
ABSTRACT: The Legal Aid, Sentencing and Punishment of Offenders Act 2012 (LASPO) made deep cuts to legal aid in the UK from April 2013, withdrawing state aid from almost all private family law cases. The paper is based on the findings of a micro-study of solicitors and Citizens Advice Bureaux (CABx) in Kent and London to investigate the impact of LASPO cuts on their work. The findings suggest that: legal aid firms have closed or merged; legal aid work is often partially carried out in solicitors' own time; 'unbundled' services for litigants in person (LIPs) are increasingly common; and family cases are being complicated and extended by the new ubiquity of the LIP. Respondents suggest that litigants may increasingly be 'giving up' on pursuing their cases, with clear implications for financial justice and contact with children. Further research is needed into the financial and affective impact of the cuts and the distribution of losses and difficulties between genders. The study, however, suggests the likelihood of post-separation poverty, debt and capital losses increasing in the post-LASPO environment, and that firms and CABx are having to find various methods of dealing with clients abandoned by the state.